PSYCHOLOGICAL ASPECTS OF ETHICAL ATTITUDES IN STUDENTS BASED ON AXIOLOGICAL APPROACHES (American Journal of Interdisciplinary Research and Development, 2023)
This article examines the psychological aspects of moral relations among students on the basis of axeological approaches, as well as the issue of the formation of moral relations of young students.